Platform economy in South America: the case of Chile, Argentina and Uruguay - Calispa-Aguilar, Evelyn; Bedoya, Ever; Tabares, Alexander (Tec Empresarial, 2025)
Digital platforms have reshaped traditional business landscapes and transformed business ecosystems globally, especially through the facilitation of online trade and access to different digital services. The platform economy emerges as an economic model in which platform companies play a dominant role in current economic and social activity as main intermediaries in facilitating interactions and transactions between different groups of users. This study explores the dynamics of the platform economy in Chile, Argentina, and Uruguay using data from the Digital Platform Economy Index (DPE Index) 2020. Chile, Argentina, and Uruguay are developed South American economies that have demonstrated a great competitive capacity for digital entrepreneurship. The study also analyzes the relative position of these countries in Latin America and globally. The findings highlight different configurations of economies. On the one hand, Chile, Argentina and Uruguay share a strong digital rights scheme, but they face particular difficulties. Chile grapples with low digital literacy among its citizens, Argentina faces barriers in financial facilitation, and Uruguay lags behind in digital freedom. This study also offers practical recommendations for public policies aimed at addressing country-specific weaknesses and strengthening the digital ecosystem in each case.